Pemanfaatan Media Video Pembelajaran Berbasis Wondershare Filmora Dalam Meningkatkan Minat Belajar Siswa Tuna Grahita Ringan - Yohana Fransiska Mai Muri; Rudy Sumiharsono; Eges Triwahyuni (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to describe the use of video-based learning media using Wondershare Filmora software at SLB Bhakti Luhur, Malang city. The approach in this research is qualitative research, full participation, interviews and direct observation. The object of research is class VIII students with mild intellectual disabilities at SLB Bhakti Luhur, Malang city. Jember. The data collection techniques used observation, interview and documentation techniques with data analysis using qualitative data analysis procedures. The results of the research show that video-based learning media using Wondershare Filmora software can increase students' interest in learning in class VIII SLB Bhakti Luhur Malang, by utilizing the power of visualization and involvement. students, Filmora can increase learning interest, learning effectiveness and motivate students to learn more actively.